Intermolecular Stereoselective Iridium-Catalyzed Allylic Alkylation: An Evolutionary Account - Shockley, Samantha E.; Hethcox, J. Caleb; Stoltz, Brian M. (Synlett, 2018)
Our lab has long been interested in the development of methods for the creation of enantioenriched all-carbon quaternary stereocenters. Historically, our interest has centered on palladium-catalyzed allylic alkylation, though recent efforts have moved to include the study of iridium catalysts. Whereas palladium catalysts enable the preparation of isolated stereocenters, the use of iridium catalysts allows for the direct construction of vicinal stereocenters via an enantio-, diastereo-, and regioselective allylic alkylation. This Account details the evolution of our research program from inception, which focused on the first iridium-catalyzed allylic alkylation to prepare stereodyads containing a single quaternary stereocenter, to our most recent discovery that allows for the synthesis of vicinal quaternary centers.1 Introduction2 Synthesis of Vicinal Tertiary and All-Carbon Quaternary Stereocenters via Enantio- and Diastereoselective Iridium-Catalyzed Allylic Alkylation2.1 Cyclic Nucleophiles2.2 Acyclic Nucleophiles2.3 Alkyl-Substituted Electrophiles3 Umpoled Iridium-Catalyzed Allylic Alkylation Reactions3.1 Tertiary Allylic Stereocenters3.2 Quaternary Allylic Stereocenters4 Synthesis of Vicinal All-Carbon Quaternary Centers via Enantioselective Iridium-Catalyzed Allylic Alkylation5 Summary and Future Outlook
Keywords: iridium; asymmetric catalysis; enantioselective; allylic alkylation; quaternary stereocenters; umpolung